New technologies in aquaculture : improving production efficiency, quality and environmental management - Burnell, Gavin; Allan, Geoff L. (Geoffrey Laurence) (Woodhead Publishing in food science, technology, and nutrition., 2009)
"With well-known editors and an international team of contributors, New Technologies in Aquaculture begins by focusing on the genetic improvement of farmed species and control of reproduction then reviews key issues in health, diet and husbandry, such as the control of viral and parasitic diseases, diet and husbandry techniques to improve disease resistance, advances in diets for particular fish species and the impact of harmful algal bloom on shellfisheries aquaculture. It examines the design of different aquaculture production systems, including offshore technologies, tank-based recirculating systems and ponds, and key environmental issues and concludes with coverage of farming new species."--Jacket